MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN CERITA DONGENG MENGGUNAKAN MEDIA BERGAMBAR PADA MATA PELAJARAN BAHASA INDONESIA - Raisa Yusi Humaira; Dedi Heriyadi; Geri Syahril Sidik (LPPM Universitas Bina Bangsa, 2022)
The low reading comprehension ability of grade III students of SD Negeri Panyingkiran Tasikmalaya has encouraged researchers to conduct Classroom Action Research (CAR) at the SD. With the formulation of the problem: How to improve learning to read understanding of fairy tales using pictorial media in grade III SD Negeri Panyingkiran? The purpose of this study was to improve the reading comprehension skills of fairy tales by using pictorial media in grade III SD Negeri Panyingkiran. This research method refers to the classroom action research method according to Kemmis & MC Taggart which includes: 1) Planning, 2) Action, 3) Observation, 4) Reflection. This research lasted for two cycles consisting of cycle I and cycle II. The results showed that the ability to read understanding of fairy tales in pre-action reached an average value of 48,84, teh first cyle increased with an average value of 54,41 and the second cycle increased with an average value of 80,76. It can be concluded that the use of pictorial media can improve the process of reading comprehension of fairy tales